1999
DOI: 10.1017/s0012162299001267
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-modulation disruption, electrodermal responses, and functional behaviors

Abstract: It was hypothesized that children clinically identified with sensory-modulation disruptions (SMD) would have atypical physiological responses to sensation, and that such responses would predict parent-reported behavioral responses to sensation. Nineteen children with clinically identified disruptions, aged 3 to 9 years, mean 6.0 years, and 19 age- and sex-matched healthy (control) children, aged 3 to 9 years, mean 6.6 years, were examined. The subjects were presented with five stimuli. Ten trials were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
193
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(209 citation statements)
references
References 25 publications
12
193
0
4
Order By: Relevance
“…Children with a behaviorally diagnosed SPD have increased electrodermal responses and habituate slower on a series of sensory stimuli (McIntosh et al 1999), show different Event Related Potential patterns (Davies and Gavin 2007), and differ in their parasympathetic responses (Schaaf et al 2003) compared to children without a clinically identified SPD. There is also preliminary evidence in support of genetic susceptibility for SOR behaviors.…”
Section: Sor Symptoms Mechanism and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Children with a behaviorally diagnosed SPD have increased electrodermal responses and habituate slower on a series of sensory stimuli (McIntosh et al 1999), show different Event Related Potential patterns (Davies and Gavin 2007), and differ in their parasympathetic responses (Schaaf et al 2003) compared to children without a clinically identified SPD. There is also preliminary evidence in support of genetic susceptibility for SOR behaviors.…”
Section: Sor Symptoms Mechanism and Prevalencementioning
confidence: 99%
“…Findings from this study suggest that the prevalence of SPD is 5% to 13% in children 4 to 6 years old ( n =710), depending on whether non-responders are considered negative for SPD or not. It is unclear how many of these children specifically experienced SOR, a subset of SPD, although McIntosh et al (1999), who applied the same Short Sensory Profile cutoff for defining SPD, note that most of their participants with SPD had SOR. In addition, Ahn and colleagues had a 39% return rate thus results may not be representative of the population of preschoolers.…”
Section: Sor Symptoms Mechanism and Prevalencementioning
confidence: 99%
“…It would be intriguing in future work to examine these same variables in each group separately. It would also have been interesting to look at SOR within each sensory system because the literature suggests that responsiveness across sensory systems has some consistency (McIntosh, Miller, Shyu, & Hagerman, 1999) or can differ substantially (e.g., Liss et al, 2006). The available data set for the current analysis did not allow for these more detailed analyses.…”
Section: Limitationsmentioning
confidence: 99%
“…Sensory processing disorders are regulatory disorders characterized by atypical responses to non-noxious sensory stimulation (Ayres 1972). A core deficit in sensory processing disorders is difficulty suppressing irrelevant sensory stimuli and showing inappropriately high aversive behavioral responses to those stimuli, including lack of habituation (Baranek and Berkson 1994; Davies et al 2009; McIntosh et al 1999; Miller et al 1999a; Parush et al 2007). In children, sensory processing disorders are measured by parent report on standardized scales (Dunn 1999), by standardized clinical assessments such as the Miller Assessment for Preschoolers and the Sensory Integration and Praxis Tests (Ayres 1989; Miller 1988) and by laboratory procedures involving exposure to repeated sensory stimulation while the child is engaged in a task.…”
Section: Domains Affected By Prenatal Alcohol Exposurementioning
confidence: 99%
“…Primate studies have employed an assessment of tactile sensory responsivity for monkeys, using a procedure adapted from human studies of sensory processing disorder (Baranek and Berkson 1994; McIntosh et al 1999). Human laboratory studies of sensory processing disorder administer repeated trials of tactile stimuli to the face and rate touch-aversive behaviors.…”
Section: Domains Affected By Prenatal Alcohol Exposurementioning
confidence: 99%